Manajemen Sumberdaya Air Daerah Aliran Sungai Sekampung di Antara Bendungan Batutegi dan Bendung Argoguruh, Propinsi Lampung: Kerangka Analitis Penyusunan Pola Operasional Waduk Harian - Ridwan Ridwan; Putu Sudira; Sahid Susanto; Lilik Sutiarso (agriTECH, 2013)
This paper present a technical analysis for obtaining an operating procedure of reservoir referred  to water level reservoir and daily water availability at stream flows.  Reservoir water level conditions Batutegi since starting operations in 2004 has never reached the normal elevation (+274 m), allegedly as a result of the decline in reservoir inflow discharge Batutegi on one side and on the other hand an increase in outflow discharge to meet the demand (demand) irrigation water by the dam Argoguruh. The increasing demand for water in the dam due to declining Argoguruh Sekampung river discharge from the dam catchment Argoguruh.  Management of water resources between the two buildings is not optimal water resources to meet a variety of needs, especially irrigation.  The objectives were to  promote a watershed resources management system analysis which has two water buildings connected functionally and  formulating reservoir daily operational pattern based on the consideration of the water availability at reservoir and river as one integrated water resources management system.  Technical analisys which were proposed is the combination of empiric formula approach and SWAT model utilization calibrated to predict water yield of the basin.  Technical analysis is done by stages in the process of succession, namely (1) caliberation SWAT model, (2) Analysis of Water Yield, (3) analysis of streamflow (river routing), (4) analysis of river water availability (supply), (5) Analysis of water demand, (6) analysis of water supply reservoirs, and (7) analysis of needs release. Results of the analysis technique was tested by studying the behavior of water supply reservoirs (reservoir routing) test the accuracy of water allocation and use of test reliability with a minimum target of 80%. This analysis method will acquire water availability at reservoir, daily discharge of stream flow, daily release from reservoir, and a new concept for arrange of Standard Operating Procedure (SOP) of reservoir.ABSTRAKMakalah ini menyajikan suatu teknis analisis yang baru dalam penentuan pola operasi (SOP: Standar Operasi Prosedur) waduk Batutegi harian. Elevasi muka air waduk Batutegi sejak mulai beroperasi pada tahun 2004 belum pernah mencapai posisi elevasi normal (+274 m),   diduga sebagai akibat semakin menurunnya debit inflow waduk Batutegi pada satu sisi dan di sisi lain terjadi peningkatan debit outflow untuk memenuhi permintaan (demand) air irigasi oleh Bendung Argoguruh.  Meningkatnya permintaan air di Bendung Argoguruh akibat menurunnya debit Sungai Sekampung yang berasal dari daerah tangkapan hujan Bendung Argoguruh.  Manajemen sumberdaya air di antara kedua bangunan sumberdaya air tersebut belum optimal untuk memenuhi berbagai kebutuhan, terutama irigasi. Tujuan penulisan makalah adalah untuk mempromosikan satu teknik analisis sistem sumberdaya air pada suatu daerah aliran sungai (DAS) yang memiliki dua bangunan air yang terhubung secara fungsional serta merumuskan pola operasional waduk harian berdasarkan ketersediaan air di waduk dan di sungai sebagai salah satu sistem pengelolaan sumberdaya air terpadu. Teknik analisis yang diusulkan menggunakan kombinasi dari penggunaan rumus empiris dan model SWAT yang sudah dikalibrasi untuk memprediksi produksi air DAS harian. Teknik analisis dilakukan dengan tahapan proses secara berturut-turut, yaitu (1) Kaliberasi Model SWAT, (2) Analisis Water Yield DAS, (3) Analisis penelusuran debit sungai (river routing), (4) Analisis ketersediaan air sungai (supply), (5) Analisis kebutuhan air (demand), (6) Analisis ketersediaan air waduk, dan (7) Analisis kebutuhan release. Hasil teknik analisis diuji dengan mempelajari perilaku ketersediaan air waduk (reservoir routing) dan uji ketepatan alokasi air menggunakan uji reliabilitas dengan target minimum 80%.  Teknik analisis yang diusulkan dapat digunakan untuk menghitung ketersediaan air pada waduk, debit aliran sungai harian sebagai informasi ketersediaan air di sungai, pelepasan debit harian dari reservoir, dan Standar Operasional Prosedur (SOP) waduk harian.